Voltage control of spin–orbit torque in Pd/Co/Pd/HfOx. (4th December 2020) - Hirai, Takamasa; Hibino, Yuki; Hasegawa, Kento; Kohda, Makoto; Koyama, Tomohiro; Chiba, Daichi
Abstract: Voltage control of current-induced spin–orbit torque (SOT) in an in-plane-magnetized Pd/Co/Pd system with a low-temperature-deposited HfO x and a gate electrode on top is studied. An application of the gate electric field to the HfO x layer is to induce a non-volatile electrochemical effect from the Pd/HfO x interface. By means of low-frequency harmonic Hall measurements, the voltage modulation of both damping-like and field-like SOT is obtained. The sign of the voltage-induced SOT modification is found to be reversed by changing the top Pd thickness. Our finding is expected to facilitate the efficient active manipulation of SOT.